Characterisation of key proteoglycans in the cranial cruciate ligaments (CCLs) from two dog breeds with different predispositions to CCL disease and rupture. (June 2021) - Allaith, S.; Tew, S.R.; Hughes, C.E.; Clegg, P.D.; Canty-Laird, E.G.; Comerford, E.J.
Highlights: Proteoglycans vary in canine cruciate ligaments at differing risk of rupture. Fibromodulin in Staffordshire bull terrier ligaments may indicate compressive loads. Elevated decorin and ADAMTS-4 genes in Greyhound ligaments suggested repair. Abstract: Cranial cruciate ligament disease and rupture (CCLD/R) is one of the most common orthopaedic conditions in dogs, eventually leading to osteoarthritis of the stifle joint. Certain dog breeds such as the Staffordshire bull terrier have an increased risk of developing CCLD/R. Previous studies into CCLD/R have found that glycosaminoglycan levels were elevated in cranial cruciate ligament (CCL) tissue from high-risk breeds when compared to the CCL from a low-risk breed to CCLD/R. Our objective was to determine specific proteoglycans/glycosaminoglycans in the CCL and to see whether their content was altered in dog breeds with differing predispositions to CCLD/R. Disease-free CCLs from Staffordshire bull terriers (moderate/high-risk to CCLD/R) and Greyhounds (low-risk to CCLD/R) were collected and key proteoglycan/glycosaminoglycans were determined by semi-quantitative Western blotting, quantitative biochemistry, quantitative reverse transcription polymerase chain reaction, and immunohistochemistry. Gene expression of fibromodulin ( P  = 0.03), aggrecan ( P  = 0.0003), and chondroitin-6-sulphate stubs ( P  = 0.01) were significantly increased, and for fibromodulin this correlated with an increase in protein content in Staffordshire bull terriers compared to Greyhound CCLs ( P  = 0.02). Decorin ( P  = 0.03) and ADAMTS-4 ( P  = 0.04) gene expression were significantly increased in Greyhounds compared to Staffordshire bull terrier CCLs. The increase of specific proteoglycans and glycosaminoglycans within the Staffordshire bull terrier CCLs may indicate a response to higher compressive loads, potentially altering their risk to traumatic injury. The higher decorin content in the Greyhound CCLs is essential for maintaining collagen fibril strength, while the increase of ADAMTS-4 indicates a higher rate of turnover helping to regulate normal CCL homeostasis in Greyhounds.